2018
DOI: 10.1038/s41598-018-34152-w
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic landscape of seminal plasma associated with dairy bull fertility

Abstract: Male fertility is the ability of sperm to fertilize the egg and sustain embryo development. Several factors determine the fertilizing capacity of mammalian sperm, including those intrinsic to sperm and components of the seminal plasma. The present study analyzed the seminal fluid proteome of Bos taurus and potential associations between proteins and fertility scores. Mass spectrometry coupled with nano HPLC allowed the identification of 1,159 proteins in the dairy bull seminal plasma. There were 50 and 29 semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 77 publications
(84 reference statements)
6
67
1
1
Order By: Relevance
“…In our study, less sperm DNA damage during storage was associated with higher levels of TIMP‐2. Similarly, high levels of TIMP‐2 are associated with low levels of sperm DNA fragmentation in men (Belardin et al, ) and high fertility in bulls (McCauley, Zhang, Bellin, & Ax, ; Viana et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, less sperm DNA damage during storage was associated with higher levels of TIMP‐2. Similarly, high levels of TIMP‐2 are associated with low levels of sperm DNA fragmentation in men (Belardin et al, ) and high fertility in bulls (McCauley, Zhang, Bellin, & Ax, ; Viana et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that spermatozoa from NPR‐B mutant mice were not attracted by NPPC, preventing fertilisation in vivo. Furthermore, the proteomic analysis showed that NPPC is more abundant in the seminal plasma of high‐fertility bulls than that in low‐fertility bulls (Viana et al, ). In our study, we observed NPPC immunoreactivity in all the epithelial cells of the epididymis and smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kong et al () reported that NPPC regulates the oocyte attraction of the spermatozoon in the oviduct. In addition, proteomic studies in cattle spermatozoa have shown that NPPC is significantly higher in bulls with high fertility (Viana et al, ). Although many studies are available on the expression of NPs in the testis (Collin Lissbrant, & Bergh, ; El‐Gehani et al, ; Pereira, Costa, Rosa‐e‐Silva, Vieira, & dos Reis, ), data on their expression in the epididymis are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…MMP2 is involved in the remodelling of the sperm membrane during epididymal maturation (Martins et al, ). TIMP‐2 is also a heparin‐binding protein (McCauley et al, ) that interacts with the seminal plasma protein BSP5 and both are described in bulls with higher fertility (Viana et al, ). In our results, we found that TIMP‐2 was upregulated in bovines, which can explain the increased fertility rate in this species compared with buffaloes.…”
Section: Discussionmentioning
confidence: 99%
“…It is a key factor in spermatogenesis and can stimulate testosterone production in the testicles (Huang et al, ). The protein positively regulates the sperm motility and capacitation (Huang et al, ; Xia et al, ) and is therefore associated with increased sperm quality in cattle (Viana et al, ). In our study, we described for the first time the C‐type natriuretic peptide in buffaloes in which decreased expression of the protein was observed.…”
Section: Discussionmentioning
confidence: 99%